Marketing and entrepreneurial success in emerging markets: the nexus - Robert Kwame Dzogbenuku; Solomon Abekah Keelson (Asia Pacific Journal of Innovation and Entrepreneurship, 2019)
Purpose - This paper aims to examine the interconnection between marketing and entrepreneurship among small and medium scale enterprises in emerging markets. Design/methodology/approach - Quantitative data were obtained from 113 micro, small and medium scale enterprises (SME) into services, manufacturing and agriculture selected conveniently within the Tema metropolis, a harbour city in Ghana; however, purposive sampling was used to choose owners and managers as respondents pre-occupied with marketing and entrepreneurial roles. These voluntary informants have operated between 4 and 9 years. Findings - The study reveals a significant relationship between five dimensions of the study including market orientation and entrepreneurial success; customer orientation and entrepreneurial success; competitor orientation and entrepreneurial success; intelligence generation; and entrepreneurial success, including information dissemination and entrepreneurial success. Research limitations/implications - Blending marketing with entrepreneurial initiatives has the propensity to accelerate success for wealth and job creation for national development especially in emerging markets where poverty and under development abounds. Adoption of basic marketing principles enables local entrepreneurs to become vehicles for social re-engineering and for rapid socio-economic growth, which ultimately affects lives at the local level. The study was limited to opinion of SME managers and owners of a harbour city. Practical implications - Application of basic marketing principles influences entrepreneurial success in emerging markets (EMs) highlighting opinions of managers and owners of SMEs strategy warranting attention of stakeholders. Thus, the study validates theoretical model of how prudent marketing and entrepreneurial attitude contributes entrepreneurial success. It also provides a new perspective on marketing principles and success in emerging markets. Social implications - Consciously incorporating basic marketing principles into operations of MSMEs will impact performances; hence, social lives of entrepreneurs will be affected positively. Originality/value - This study being among the few in sub-Saharan Africa highlights how application of marketing principles to entrepreneurial operations is a vital role in growing local MSMEs unto the world stage. Therefore, blending basic marketing principles with entrepreneurial initiatives will accelerate wealth and job creation and national development to achieve the world's sustainable development goals aimed at reducing poverty.